Small-scale fisheries as a vehicle for rural development : a case study of two villages in the former Ciskei, Eastern Cape Province, South Africa - Seti, Simpiwe (Rhodes University, Faculty of Humanities, Department of Sociology and Industrial Sociology, 2003)
This thesis examines small-scale rural fisheries which were initiated in two villages by the Department of Ichthyology and Fisheries in conjunction with the Institute of Social and Economic Research in 1997. The main objective for undertaking the study was to determine the potential of the fisheries to serve as viable and sustainable options that could contribute towards rural development in the area of study. To examine the contribution made by the small-scale fisheries towards rural development in the villages, it is imperative to have an understanding of the context in which they were established as well as the prospects for sustainable development. It is argued in this study that despite the significant contribution made by inland rural fisheries in improving rural livelihoods they are still accorded minimal support and attention in South Africa. As an illustration of the important role played by rural fisheries, case studies from Malawi and Zimbabwe have been drawn into the study with a view to providing lessons for rural areas of South Africa. The study took place at a time when natural resources in the villages were significantly declining and environmental degradation reaching uncontrollable proportions, so there is an urgent need to secure an alternative mode of subsistence for the population in the villages. Development interventions by the state and non-governmental organisations in the study area have not been sustainable and they collapsed within a short period of time. A case in point is the Tyefu irrigation scheme, which was initiated in the villages but, owing to various factors, it failed leaving the villagers with a diminished mode of subsistence, thus providing the impetus for the implementation of small-scale rural fisheries. In order for small-scale fisheries to be sustainable it is essential to adopt models that are aimed at sound natural resource use and management. This study has raised various issues pertinent to natural resource use and management in the study area. A model for management of natural resources that involves and aims to empower local communities in the management of the fisheries is presented in the study. It has also been demonstrated that rural fisheries in the study area comply with the model. Finally, the study draws the conclusion that small-scale fisheries in the villages contribute towards rural development, however, there are constraints that need to be eradicated.
Keywords: Small-scale fisheries -- South Africa -- Eastern Cape; Fisheries -- South Africa -- Eastern Cape; Fishes -- South Africa -- Eastern Cape; Rural development -- South Africa -- Eastern Cape; Fish trade -- Developing countries; Fisheries, Cooperative -- Developing countries